A Glossary of Political Theory - John Hoffman (Edinburgh University Press, 2007)
This essential reference covers alphabetically both the major concepts in political theory and the key writers in the field. While ensuring accuracy and objectivity, the entries represent interpretations that are both challenging and interesting. The premise underlying the book is that politics cannot be studied without theory, and for students, the more concrete and relevant the theory, the better. Presenting theory in an abstract fashion makes it daunting for students who can find it difficult to see the links between theory and practice. The definitions in this glossary therefore relate political ideas to political realities (i.e. everyday controversies) in an attempt to make them as lively, stimulating, and accessible as possible. Terms have been selected based upon the concepts most regularly used in teaching.